Exploring Students’ Mathematical Literacy Through Learning Styles and School Environment - Handoko, Hendri; Mubarikah, Anti (Universitas Negeri Surabaya, 2025)
This study aims to analyze students' mathematical literacy skills in relation to their learning styles (visual, auditory, and kinesthetic) and their school learning environment. A mixed-methods approach was employed, using mathematical literacy tests, student response analysis, and in-depth interviews. The results show that visual learners excel in numerical representation and written communication but struggle with formal symbolism without visual support. Auditory learners understand procedures well through verbal explanations but have difficulty constructing arguments and alternative strategies. Kinesthetic learners perform well on contextual problems through practical activities but are weak in visual representation and formal reasoning. A non-varied and unresponsive learning environment hampers the development of mathematical literacy. These findings emphasize that a mismatch between learning styles and instructional approaches negatively affects literacy achievement, particularly in reasoning, argumentation, and representation. Therefore, fostering a learning environment that accommodates diverse learning styles is essential for enhancing students’ overall mathematical literacy.